2019
DOI: 10.1016/j.molbiopara.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of reduced sensitivity to praziquantel in Schistosoma mansoni

Abstract: Schistosomiasis is an intravascular parasitic infection estimated to affect over 206 million people, the majority of whom live in Africa where the trematode worms Schistosoma mansoni and Schistosoma haematobium are the major causative agents. While a number of drugs have been used to treat schistosomiasis, praziquantel (PZQ) is the only one that is widely available, relatively cheap, and easy to use. The reliance on a single drug for the treatment of such a prevalent disease is a cause for concern due to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…Our study found altered expression of the same protein or proteins with similar function; heat shock protein 70 (O45039) and sodium/potassium-transporting ATPase subunit alpha (A0A095AFH4, A0A094ZR23) ( Table S1 ,2). Furthermore, gene expression profiling of less-susceptible parasite indicated a list of gene involving with calcium signaling pathway (calcium binding protein, calmodulin, calponin) and oxidative stress response (thioredoxin and superoxide dismutase) [ 36 ]. Our mass spectrometric data also found proteins in those pathways, which were 20 kDa calcium-binding protein (A0A095A3D3), putative annexin (G4VL68), voltage-dependent anion-selective channel protein (VDAC) (G4M1U8) for calcium signaling pathway and tryparedoxin peroxidase (C1LV40), glutathione-S-transferase (Q26513) for oxidative stress pathway ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our study found altered expression of the same protein or proteins with similar function; heat shock protein 70 (O45039) and sodium/potassium-transporting ATPase subunit alpha (A0A095AFH4, A0A094ZR23) ( Table S1 ,2). Furthermore, gene expression profiling of less-susceptible parasite indicated a list of gene involving with calcium signaling pathway (calcium binding protein, calmodulin, calponin) and oxidative stress response (thioredoxin and superoxide dismutase) [ 36 ]. Our mass spectrometric data also found proteins in those pathways, which were 20 kDa calcium-binding protein (A0A095A3D3), putative annexin (G4VL68), voltage-dependent anion-selective channel protein (VDAC) (G4M1U8) for calcium signaling pathway and tryparedoxin peroxidase (C1LV40), glutathione-S-transferase (Q26513) for oxidative stress pathway ( Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…We suspect that standing variation for PZQ resistance is also likely, because this trait is easy to select in the laboratory. This has been done by several groups using independent laboratory populations, and resistance has spread within very few generations [4954], strongly suggesting that resistance alleles were already present in these laboratory populations. Furthermore, the laboratory populations used for selection were isolated before PZQ was available [23,55] and so were not exposed to drug selection.…”
Section: Discussionmentioning
confidence: 99%
“…Kunitz-type protease inhibitors have also been found in the secretomes of other parasitic flatworms [62,63], and shown to act as ion channel blockers [64] and inhibitors of dendritic cell activation [65]. Additionally, laboratory strains of S. mansoni selected for PZQ resistance show altered expression of a various Kunitz-type protease inhibitors, indicating these may be involved in drug resistance [42].…”
Section: Pzq Causes Changes In Mrna Levels Of Putative Immunomodulatomentioning
confidence: 99%